1993
DOI: 10.1515/zna-1993-1009
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Fullerenes by Circumscribing

Abstract: An algorithm for the generation of fullerenes with isolated pentagonal rings by successively circumscribing base excised internal structures with a combination of pentagonal and hexagonal rings is detailed. The presence of adjacent bay regions is a necesary and sufficient condition for preculding this circumscribing operation for a polypent/polyhex system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…27 A general procedure for drawing planar graphs is Tutte 's baricentric method. 28 Dias 29,30 has produced a circumscribing algorithm for construction of planar graphs (Schlegel diagrams) of fullerene polyhedra and has shown, 30 by generating all the C 84 fullerenes, that his scheme is perfectly general. To get an isolated pentagon fullerene of desired symmetry Dias's scheme can easily be used with purposeful manipulation.…”
Section: Introductionmentioning
confidence: 99%
“…27 A general procedure for drawing planar graphs is Tutte 's baricentric method. 28 Dias 29,30 has produced a circumscribing algorithm for construction of planar graphs (Schlegel diagrams) of fullerene polyhedra and has shown, 30 by generating all the C 84 fullerenes, that his scheme is perfectly general. To get an isolated pentagon fullerene of desired symmetry Dias's scheme can easily be used with purposeful manipulation.…”
Section: Introductionmentioning
confidence: 99%
“…In general, Schlegel diagrams of fullerenes with rotational symmetry in this work can be generated by starting with a core cyclic C4, C5, C6 carbon ring and circumscribing it with a layer of 4, 5, 6 pentagonal rings, respectively. This first step is done for all the series in Figures –, which gives the initial cap. The last step always involves circumscribing with a layer of pentagonal rings equal in number with those in the first step to give the final endcap.…”
Section: Resultsmentioning
confidence: 99%
“…Small fullerenes and nanotubes related to this study include work by Lu and Chen . Generating fullerenes and nanotubes by circumscribing is simple and general and may be compared to the recently published recursive generation of IPR fullerenes . The efficient factorization of the characteristic polynomials of highly symmetrical fullerenes like C 60 Buckminsterfullerene has been described. , A highly mathematical determination of characteristic polynomials and eigenvalues has recently been reported .…”
Section: Introductionmentioning
confidence: 99%
“…In a qualitative way, two different algorithms such as circumscribing [15] and leapfrogging [16] for the generation of the fullerenes have been proposed. Dias [17] constructed the five IPRs of C 78 by taking the circumscribing algorithm. The five C 78 IPR isomers are labelled as A(D 3h ), B(C 2v ), C(C 2v ), D(D 3 ) and E(D 3h ), and their structures are drawn in figure 1.…”
Section: Calculationsmentioning
confidence: 99%
“…Due to their shell structures, the curved connections among the carbon atoms cause the misalignment of two π-orbitals (figure 2(a)) at the adjacent carbon atoms in the path of conjugation and somewhat reduce the π -orbital overlap and aromatic character. Hence, the IPR structures are more favourable in energy than those containing adjacent five-member rings because they minimize both antiaromaticity and strains [17]. Dias [17] has suggested that it is always desirable to derive a structure where strain is distributed as uniformly as possible following the principle of the 'neighbour index' of a ring [32].…”
Section: Curvature Of a Fullerene And The Third-order Polarizabilitymentioning
confidence: 99%